2008
DOI: 10.1093/aob/mcn203
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous ethylene inhibits sprout growth in onion bulbs

Abstract: Exogenous ethylene proved to be a powerful inhibitor of sprout growth in onion bulbs. The dormancy breaking effect of 1-MCP indicates a regulatory role of endogenous ethylene in onion bulb dormancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
2
24
1
1
Order By: Relevance
“…Comparison between onions stored in continuous air or ethylene revealed that those stored in ethylene had reduced sprout growth, which is consistent with similar previous work (Bufler, 2009). Reduced sprout growth in response to continuous ethylene storage was also supported by the microarray data.…”
Section: Sprout Suppression Through Exogenous Ethylene Down-regulatessupporting
confidence: 90%
See 2 more Smart Citations
“…Comparison between onions stored in continuous air or ethylene revealed that those stored in ethylene had reduced sprout growth, which is consistent with similar previous work (Bufler, 2009). Reduced sprout growth in response to continuous ethylene storage was also supported by the microarray data.…”
Section: Sprout Suppression Through Exogenous Ethylene Down-regulatessupporting
confidence: 90%
“…Bufler (2009) found that Copra onions held in continuous ethylene (10.6 mL L 21 ) had reduced sprout growth compared with those held in air. Surprisingly, treatment with 1-MCP for 24 h after curing (6 weeks at 28°C prior to cold storage) reduced sprout growth in SuperSweet1 onions when stored at 4°C or 12°C (Chope et al, 2007a).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For comparison, 20 % of bulbs of the next most storable cultivars 'Magic Gold' and 'New Turbo' sprouted for the same period of time (Nam et al 2011). Onset of sprouting is commonly preferred to characterize the storage life of onions because of its clear relationship to physiological processes in bulbs (Pak et al 1995;Chope et al 2007a;Yasin and Bufler 2007;Bufler 2009). In the present work, the development of inner sprouts was observed on longitudinally cut bulbs after 2 months of storage and visible sprouts appeared after 5 months in a good agreement with the above mentioned results of Nam et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…En condiciones naturales, la brotación de los bulbos de cebolla chalote ocurre luego de un cierto tiempo después de la cosecha dependiendo del genotipo y las condiciones de almacenamiento, debido a que éstos tienen un periodo de dormancia [26]. Estudios de Benkeblia y colaboradores [27] demostraron que los compuestos fenólicos interfieren indirectamente con el proceso de brotación de bulbos de cebolla y que una baja temperatura (0 • C) activa una señal para reducir fenoles, con lo cual se promueve la brotación de bulbos.…”
Section: Discussionunclassified